+0  
 
0
74
3
avatar+1397 

If f(x) = -x + 4 and g(x) = x^2 - 5, then g(f(3)) = ?

 

A) -8 
B) -4 
C) -3 
D) 0 
E) 3

 

 

If f(x) = -x^2 + 6x, what is f(-3)?

 

A)-162

B)-27

C)-9

D)9

E)162

 Dec 4, 2019
 #1
avatar+106539 
+2

If f(x) = -x + 4 and g(x) = x^2 - 5, then g(f(3)) = ?

 

We first evaluate f(3)   =   -3 + 4    =   1

 

So.....now we have   g (1)

 

Plug 1 into g  and evaluate.....that will be your answer

 

 

cool cool cool

 Dec 4, 2019
 #2
avatar+106539 
+2

For the second....evaluate

 

- (-3)^2   +  6(-3)

 

 

cool cool cool

 Dec 4, 2019
 #3
avatar+999 
0

Q1:

 

We have to do the functions inside, and work our way out.

Calculate f(3), and using the outcome, galculate the g(x) function of that.

f(3) = -3+4 = 1

g(1) = 1^2-5

 

Q2:

 

Plug in -3 into the x values

Remember, two negatives multiplied by each other equal a positive.

 

You are very welcome!

:P

 Dec 4, 2019

2 Online Users